On the superiority of a combination of aerobic and resistance exercise for fibromyalgia syndrome: A network meta-analysis - Chen, Jiping; Han, Bing; Wu, Chenggang (Frontiers in Psychology, 2022)
Abstract: Background: Fibromyalgia syndrome is the second most common chronic diffuse pain disorder and can have a lasting negative impact on the quality of life, pain, and physical function of people. Exercise therapy is an important component of the treatment of fibromyalgia, but there was not a consensus understanding of the effect of various exercise programs on the quality of life, pain, and physical function of people with fibromyalgia syndrome. This study aimed to compare three exercise programs (aerobic exercise, resistance exercise, and a combination of aerobic and resistance exercise) in their effectiveness in improving quality of life, relieving muscle pain, and enhancing physical function in patients with fibromyalgia. Methods: A comprehensive search of databases, including China National Knowledge Internet, Wan fang, The Cochrane Library, PubMed, EMBASE, and Web of Science, was conducted to identify randomized controlled trials on exercise therapy for patients with fibromyalgia syndrome with outcome indicators including at least one of Fibromyalgia Impact Questionnaire (FIQ), Tender point count (TPC), and 6-minute walk test (6MWT) from the date of database creation on 20 April 2022. The included studies were evaluated for literature quality according to Cochrane Handbook criteria, and a network meta-analysis was performed using STATA 14.0. Result: Forty-five randomized controlled trials met all inclusion criteria and were analyzed. The network meta-analysis showed that a combination of aerobic and resistance exercise was ranked first in all three dimensions of quality of life improvement, pain alleviation, and physical function enhancement (Mean Rank = 1.6, 1.2, 5.9). Conclusion: The current meta-analysis demonstrates that the combination of aerobic and resistance exercise may be the best type of exercise to accentuate the quality of life, pain alleviation, and physical function for people with fibromyalgia syndrome.